Preparation Technique of SiO2/HFE 7000 Nanorefrigerant / S. Razak ... [et al.] - Razak, S.; Nawi, M.R.M; Rehim, M.Z.A; Azmi, W.H (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Nanorefrigerant, as an engineered colloid consist of a base fluid and nanometer-sized solid particles, has drawn excessive responsiveness from researchers for its higher thermal properties and various potential applications. It can be applied in many devices for better performances. The preparation of nanorefrigerant is a foremost step in the use of nanoparticles for heat transfer performance enhancement of fluids. There are several important requirements into creating a useful nanorefrigerant. However, it is still a challenge to make a homogeneous nanorefrigerant and long-term stable, and without disturbing the thermophysical properties.